Investigating measurement invariance in PIRLS 2021 across English and isiZulu language groups - Sinethemba Mthimkhulu; Karen Roux; Maryke Mihai (Reading & Writing, 2024)
Background: PIRLS 2021 results revealed that South African Grade 4 learners performed significantly lower compared to other countries in reading comprehension and that they did not reach the standardised international mean score of 500. It was also evident from the results that English learners performed relatively higher than isiZulu learners.